Spatial disparities in death registration across states and districts of India, 2019-21 - Aditya Singh; Ananya Kundu; Sumit Ram; Rakesh Chandra; Arabindo Tanti; Shivani Singh; Vineet Kumar (BMC Public Health)
Abstract Background The persistent issue of incomplete death registration in India, with a significant number of deaths going unrecorded, underscores the critical need for a granular understanding of spatial variations. Given the nation’s vast geographic and demographic diversity, this granular understanding, particularly at the district level, is crucial for effective interventions. This analysis, therefore, aims to examine spatial disparities in death registration at both the state and district levels across India. Data and methods Using data from the fifth round of the National Family Health Survey (NFHS-5) conducted in 2019-21, this study analyzed information on 79,449 deaths occurring in the three years preceding the survey, across 707 districts in India. The study explored spatial patterns and identified clusters of death registration using Moran’s I and univariate Local Indicators of Spatial Association (LISA) maps. Additionally, spatial regression models were employed to examine the factors influencing death registration at the district level. Results In 2019-21, only 71% of deaths in India were registered, with significant variations across states and districts. The univariate Moran’s I value of 0.69 (p < 0.001) indicated strong spatial clustering in death registration at the district level. Two notable ‘cold spots’—districts with low death registration rates surrounded by other low-registration districts—were identified across 152 districts, primarily in the eastern states of Uttar Pradesh, Jharkhand, Bihar, and the northeastern regions of Arunachal Pradesh, Nagaland, and parts of Manipur. Results from regression models revealed that factors such as the proportion of poor households, rural households, Muslim and Scheduled Tribe (ST) households, and households with at least one uneducated member were negatively associated with death registration at the district level. Conclusions The findings suggest the necessity for region-specific focused interventions to improve death registration in India, taking the social determinants of death registration into consideration and raising societal awareness about it.